D/f‐Polypnictides Derived by Non‐Classical Ln2+ Compounds: Synthesis, Small Molecule Activation and Optical Properties. Issue 29 (3rd May 2021) - Reinfandt, Niklas; Michenfelder, Nadine; Schoo, Christoph; Yadav, Ravi; Reichl, Stephan; Konchenko, Sergey N.; Unterreiner, Andreas N.; Scheer, Manfred; Roesky, Peter W.
Abstract: Reduction chemistry induced by divalent lanthanides has been primarily focused on samarium so far. In light of the rich physical properties of the lanthanides, this limitation to one element is a drawback. Since molecular divalent compounds of almost all lanthanides have been available for some time, we used one known and two new non‐classical reducing agents of the early lanthanides to establish a sophisticated reduction chemistry. As a result, six new d/f‐polyphosphides or d/f‐polyarsenides, [K(18‐crown‐6)] [Cp′′2 Ln(E5 )FeCp*] (Ln=La, Ce, Nd; E=P, As) were obtained. Their reactivity was studied by activation of P4, resulting in a selective expansion of the P5 rings. The obtained compounds [K(18‐crown‐6)] [Cp′′2 Ln(P7 )FeCp*] (Ln=La, Nd) are the first examples of an activation of P4 by a f‐element‐polypnictide complex. Additionally, the first systematic femtosecond (fs)‐spectroscopy investigations of d/f‐polypnictides are presented to showcase the advantages of having access to a broader series of lanthanide compounds. Abstract : Six new d/f‐polyphosphides or d/f‐polyarsenides, [K(18‐crown‐6)] [Cp′′2 Ln(E5 )FeCp*] (Ln=La, Ce, Nd; E=P, As), were obtained by usage of non‐classical divalent lanthanide compounds as reducing agents. While their optical properties were investigated by fs‐spectroscopy, their reactivity was studied by P4 activation. The latter resulted in a selective expansion of the P5 rings ([K(18‐crown‐6)] [Cp′′2 Ln(P7 )FeCp*] (Ln=La, Nd)).